Child-Friendly Justice – Slovakian Perspective - Koromház, Peter (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract:The chapter offers a comprehensive analysis of the rights and participation of minor children in civil, criminal, and administrative court proceedings in the Slovak Republic, from a child-friendly justice perspective. The Slovak legal system does not currently contain a dedicated procedural code for minors. Relevant provisions are dispersed across multiple legal statutes, including the Civil Litigation Code, the Civil Non-Contentious Procedure Code, the Administrative Court Code, and the Criminal Procedure Code. Particular attention is paid to the Family Act and its influence on interpreting the best interests of the child in both judicial and administrative decision-making. The chapter focuses on assessing how these legal statutes address the procedural capacity, representation, and participatory rights of minors, including the right to be informed and to express their opinion.Keywords: the best interests of the child, Court, civil proceedings, criminal proceedings, administrative proceedings